Simplify (12 – 6i) – (3 – 8i)
Simplify (6 + i )(8 – 3i)
2√(x – 8) = 6
√(x + 14 +2) = x
Any help is great, thanks!
3 Answers

First question:
We change the sign of the second parenthesis so that the minus changes into plus
( 12 – 6i ) + ( 3 + 8i )
Now we remove the parenthesis as they are useless now
12 – 6i + 3 + 8i = 2i + 15
Second question:
we multiply each item in the first parenthesis with two items of the second parenthesis
( 6*8 ) + ( 18i ) + ( 8i ) + ( 3i^2 )
Now we remove parenthesis and do operations
3i – 10i + 48
Third question:
we divide both by 2
SQRT(x8) = 3
We raise both sides to the power of 2
x8 = 9
we add 8 to both sides
x = 17
The last one:
We raise both sides to the power of 2
X + 14 + 2 = X^2
we subtract (X + 14 + 2) from both sides
X^2 – X – 16 = 0
I can’t find any simpler forms.

1. Treat as vector addition (12, 6i) + (3, 8i) = (15, 2i) = 15 – 2i
2. (6+i) * (83i) = 48 + 8i – 18i – 3iÂ² = 48 + 8i – 18i + 3 = 51 – 10i
3. 2 * SQRT[ x – 8 ] = 6, SQRT[ x – 8 ] = 3, x – 8 = 9, x = 17
4 SQRT[ x + 14 + 2 ] = SQRT[ x + 16 ] = x, xÂ² – x – 16 = 0
By the quadratic formula, x = 1/2 Â± 1/2 * SQRT[ 1 + 64 ] = 1/2 Â± 1/2 * SQRT[ 65 ]

well the first is
(128i)(38i)=
12+38i+8i=15
2nd is (6+i)(83i)=
6(83i)i(83i)=
4818i+8i3isquared=
48+318i+8i=
5110i hope that helps!
Don’t know bout the others!